EMU Challenges European Labor Markets - Krieger-Boden, Christiane; Dohse, Dirk.; Soltwedel, Rudiger (Washington, D.C. : International Monetary Fund, 1999)
This paper discusses the challenges that European Monetary Union (EMU) poses for European labor markets, emphasizing in particular the regional dimension of the European unemployment problem. The authors argue that the inability of labor markets to adjust to shocks is largely a regional problem within EMU member countries, requiring structural reforms to enhance labor market flexibility but also a decentralization of competencies and greater diversity of labor market outcomes. Any attempt to successfully reform European labor markets and 'make them fit for EMU' has to take into account the regional-and even a more decentralized firm-perspective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet